Implementasi Pendidikan Karakter melalui Kurikulum Sekolah: Sebuah Kajian Literatur - Warlim, Warlim; Rozak, Abdul; Revalina, Atiqah (Jurnal Ilmiah Edukatif, 2025)
This literature review aims to analyse the implementation of character education through the school curriculum. Character education is considered essential in shaping the morals, ethics and integrity of the younger generation. In this study, various relevant studies and literature were reviewed to understand how character education is integrated into the school curriculum and what factors influence its success. The findings show that a holistic approach that incorporates character values into all subjects and school activities is the most effective. Successful implementation also depends heavily on the readiness and commitment of teachers, as well as the support of school management and clear policies. Continuous evaluation and adaptation according to the needs and context of the school is key to ensuring the effectiveness of character education. Thus, collaboration between teachers, parents, and the community is very important in shaping students' responsible and principled character. This study helps provide insight into the importance of character education and how it can be effectively implemented in a school environment.